Examining the Impact of Self-concept on Adolescents’ Self-regulated Learning: A Predictive Modeling Approach - Patricia Ayllón-Salas; José L. Arco-Tirado; Francisco D. Fernández-Martín (Psicología Educativa: Revista de los Psicólogos de la Educación)

(untitled)
The aim of the present study was to explore the relationship between self-concept and self-regulated learning in secondary education students. For this purpose, self-concept and self-regulated learning were measured in 923 participants. The results of the study suggest that academic, social, emotional, physical, and family self-concept could predict the use of self-regulated learning strategies (i.e., affective motivation and value motivation). Therefore, the constructed models explained 15% and 18% of the variance in affective motivation and value motivation, respectively. All self-concept dimensions emerged as positive predictors of affective motivation, while academic, social, family, and physical self-concepts were identified as significant predictors of value motivation. In summary, the results of this study suggest that self-concept enhances the use of self-regulated learning strategies in the academic field.